2018
DOI: 10.1186/s13104-018-3126-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the structure of a ceRNA-theoretical, bipartite microRNA–mRNA interaction network regulating intestinal epithelial cellular pathways using R programming

Abstract: ObjectiveWe report a method using functional-molecular databases and network modelling to identify hypothetical mRNA–miRNA interaction networks regulating intestinal epithelial barrier function. The model forms a data-analysis component of our cell culture experiments, which produce RNA expression data from Nanostring Technologies nCounter® system. The epithelial tight-junction (TJ) and actin cytoskeleton interact as molecular components of the intestinal epithelial barrier. Upstream regulation of TJ-cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…Genes and protein networks within the “black” module were involved in cellular regulatory processes, and many were associated with tumor formation and multiple forms of cancer. Further supporting previously identified sub-networks of genes associated with cancer and cellular proliferation through network modelling 65 . Genes in the lightcyan module were associated with cellular and tissue structure, cancer, and cardiovascular biological processes.…”
Section: Discussionsupporting
confidence: 81%
“…Genes and protein networks within the “black” module were involved in cellular regulatory processes, and many were associated with tumor formation and multiple forms of cancer. Further supporting previously identified sub-networks of genes associated with cancer and cellular proliferation through network modelling 65 . Genes in the lightcyan module were associated with cellular and tissue structure, cancer, and cardiovascular biological processes.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, these lncRNAs may serve as tumor-related prognostic indicators. Recently, Robinson and Henderson constructed a network model to identify hypothetical mRNA–miRNA interaction networks associated with epithelial function [29]. A mRNA–miRNA interaction list was generated using functional-molecular databases and network modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The authors quantified and visualized inherent network structures by using R code and identified a subnetwork containing a large number of shared, targeting miRNAs, of genes related to cancer and cellular proliferation, including cyclin D and c-MYC. The complexity of the miRNA–mRNA interaction network represents an obstacle for predicting and verifying the function of the ceRNA network [29]. The ceRNA hypothesis was proposed to explain the mechanism of tumorigenesis; this hypothesis provides a novel guiding theory and suggests valuable strategies and research directions for the diagnosis and treatment of malignancies [10].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, our panel selection utilized KEGG pathway database to generate a list of genes affecting intestinal-epithelial barrier function and epithelial homeostasis, is also described in terms of a network interaction model for miRNA-mRNA interactions. 24 Genes were selected from KEGG Pathways for tight-junction (map04530), regulation of actin cytoskeleton (map04810), colorectal cancer (map05210), most with significant overlapping membership in adherens junction (map04520), focal adhesion (map04510), Wnt (map04310), and other pathways. 25 Genes from the initial list were excluded if not expressed in lower GI tissues by referencing against the Human Protein Expression Atlas (which includes tissue-specific RNA expression).…”
Section: Rna Extractionmentioning
confidence: 99%